Occurrences of pinnipeds (Carnivora, Phocidae) in the Azores archipelago (Portugal) - Barcelos, Luis M. D. (2022)
An inventory of historical and actual occurrences of pinnipeds in the Azores archipelago. The data used come from Silva et al. (2009) and from RACA - Rede de Arrojamentos de Cetáceos dos Açores (RACA-DRAM-RAA).